EFEKTIVITAS KOMPRES HANGAT TERHADAP RESPON NYERI IMUNISASI PENTABIO DI WILAYAH PUSKESMAS PEKAUMAN BANJARMASIN - Kusvitasari, Hairiana; Novalia Widya Ningrum; Agustin Criselly Leluni (LPPM Universitas Sari Mulia, 2023)
Background: One of the side effects of vaccination is pain from needle injections, with intramuscular injections in infants being more painful than injections in other areas. Pain responses due to vaccination can cause trauma in children, where events that result in fear, anger, or pain are common traumatic experiences. The side effects of immunization are referred to as AEFI (Adverse Events Following Immunization), such as fever, swelling at the injection site, redness, pain at the injection site, and fatigue. At Pekauman Community Health Center (Puskesmas Pekauman) in Banjarmasin, based on interviews with midwives providing immunization services, none have offered non-pharmacological therapies such as warm compresses to manage injection-related pain and swelling. Objective: To determine the effectiveness of warm compress therapy on the pain response following Pentabio immunization in the working area of Puskesmas Pekauman. Method: The research method used was a quasi-experimental one-group design without a control group, analyzed using the Wilcoxon test. The instrument used was the FLACC pain scale questionnaire, measured before and after the warm compress was applied to infants following Pentabio immunization. The study sample consisted of 15 infants, selected using simple random sampling. Results: The Wilcoxon test showed a p-value of 0.001 (<0.05). Conclusion: Warm compress therapy is proven to be effective in reducing the pain response following Pentabio immunization in the working area of Puskesmas Pekauman. Keywords: Warm Compress, Pain Response, Immunization